Peningkatan Hasil Belajar Siswa Menggunakan Model Talking Stick di Kelas V Sekolah Dasar - Muhammad Ridwan; Desyandri Desyandri; Yanti Fitria (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the improvement of student learning outcomes in learning IPS using Talking Stick learnig model in the fifth grade of elementary school. The type of research used is Class Action Research using qualitative and quantitative approaches. Subjects in this study were teachers and fourth grade elementary school students totaling 20 people. The research was carried out in two cycles with planning, implementation, observation and reflection procedures. The results showed that the learning of IPS using Talking Stick learnig model can improve student learning outcomes in SD Negeri 07 Sentosa Padang Gelugur Pasaman District.